Conventional and Doppler ultrasound for the differentiation of benign and malignant canine mammary tumours - Feliciano, M. A. R. [UNESP]; Vicente, W. R. R. [UNESP]; Silva, M. A. M. [UNESP] (Wiley-Blackwell, 2012)
Objectives: The aim of this study was to evaluate the sensitivity of conventional and Doppler ultrasound for differentiation of benign and malignant mammary tumours in female dogs. Methods: Mammary tumours were evaluated from 60 animals and divided into two distinct groups, group 1 (benign tumours) and group 2 (malignant tumours). The tumours were assessed by conventional ultrasound, Doppler ultrasound mode, histopathology and immunohistochemical detection of vascular endothelial growth factor. Results: Conventional ultrasound examination was found to be ineffective in separating tumours into the two experimental groups. Similarly, using colour-flow Doppler ultrasound, no correlation was found between the presence of vascularisation and its characteristics between the two groups. Triplex Doppler ultrasound yielded average maximum velocities of 28.71 cm/s for malignant and 19.91 cm/s for benign tumours, which were significantly different (P=0.01). For vascular endothelial growth factor, an average score of 2.22 was found for group 2 and 1.66 for group 1 (P=0.03). Positive correlations were found between vascular endothelial growth factor and presence of vascularisation (P=0.04 and r=0.3658) and between vascular endothelial growth factor and maximum velocity (P=0.03 and r=0.3913). Clinical Significance: Doppler evaluation may be used to predict malignancy of mammary tumours in bitches.